THE ESTIMATION OF BREEDING VALUE OF BALI CATTLE BODY WEIGHT AT BALAI PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK (BPTU-HPT) DENPASAR - N., Hilalah; Ardika, I N.; Warmadewi, D. A. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
Breeding value is one of on the selection program parameters which can be used to evaluate to improve genetic quality of cattle.   BPTU-HPT Denpasar is goverment institution responsible in conserving bali cattle. This study was conducted to find out breeding value of birth weight, weaning weight and yearling weight calves in that institution. Data used in this study was secondary data collected from year 2012 to 2015. This study was carried out from July 14 th to August 25 th 2017.  From those data, breeding value estimation of birth weight, weaning weight and yearling weight were collected. Calculation method used base on performance test by Hardjosubroto (1994). The results showed that breeding value of those parameter observed vary from upper and bellow average of the population year 2012 to 2015. The highest breeding value estimation of birth weight breeding ob tained was 0.46 kg (bulls number 0105.15 and 0110.15) on male calves, while as on female calves was 1.40 kg (cow number 0204.15) in 2015. Secondary parameter weaning weight was 9.94 kg (bull number 0137.13) on male calves and 9.90 kg (cow number 0233.13) on female calves in 2013. The last parameter calculated, yearling weight the highest breeding value estimation of male and female calves were 6.99 kg (bull number 0101.14) and 5.30 kg (cow number 0204.14) in 2014. Those calves which were have high breeding values, will be suggested to be replacement for culled cattle. Keywords : bali cattle, body weight, breeding value